Employee Engagement as a Moderating Variable of the Influence of Resonant Leadership on Employee Performance - Ahmad Abroza; Teguh Setiawan Wibowo; Rieneke Ryke Kalalo; Amelia Anwar; Nety Kumalasari (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This research is a quantitative study with an explanatory approach. The data used in this study is primary data obtained by the researcher from 335 Mandala Finance employees spread throughout Indonesia. The data obtained by the researcher was analyzed using the smart PLS 4.0 analysis tool. The result in this article show that The first hypothesis in this study aims to determine whether Resonant Leadership Style can have a positive relationship and a significant influence on Employee Performance variables. This is because the P-Values ​​in this article are positive and have a value below the 0.05 significance level, namely 0.003. These results indicate that Resonant Leadership Style can make employees more obedient, more compliant, company targets and visions can be easily achieved, can make the company stable, and ultimately can improve Employee Performance.. However, the results in this study show even more significant results. The researchers believe this is because the selection of Resonant Leadership Style as an independent variable is different from the five studies above which only used General Leadership Style as an independent variable. In addition, the second hypothesis in this study can also be accepted because the P-Values ​​are positive and below the significance level of 0.05, which is 0.000, which is more significant than direct testing. Based on this, it can be concluded carefully that employee involvement can also help and even strengthen the influence of the Employee Involvement variable on Employee Performance because employees who are increasingly involved in company activities can make employee skills increase so that if this is accompanied by a Resonant Leadership Style, it can make Employee Performance even more significantly increase.